Haiti : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2014)
This paper focuses on Haiti's Poverty Reduction Strategy Paper and 2014-2016 Three-Year Investment Program. The Haiti Strategic Development Plan presents the new framework for the planning, programming, and management of Haitian development, the vision and the strategic guidelines for the country's development, and the four major work areas to be implemented to ensure the recovery and development of Haiti. The Three-Year Investment Program, 2014-2016 (PTI 2014-2016) concerns implementation of the Strategic Plan for Development of Haiti and more specifically implementation of the government's priorities for the period.